1977
DOI: 10.1093/nar/4.11.3839
|View full text |Cite
|
Sign up to set email alerts
|

Structural transition in chromatin induced by ions in solution

Abstract: Structural transition in chromatin was measured as a function of counter ions in solution (NaCl or MgCl(2)) and of histones bound on the DNA. The addition of counter ions to aqueous solutions of chromatin, partially dehistonized chromatin, and DNA caused a drastic reduction in viscosity and a significant increase in sedimentation coefficient. Transitions occurred primarily at about 2 x 10(-3) M NaCl and 1 x 10(-5) M MgCl(2) and are interpreted as a change in structure of chromatin induced by tight binding of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The early and important work of Zubay and Doty (22) showed that the intrinsic viscosity and light scattering do not vary in a plateau between .5 and 1.5 mM salt, but that at higher concentrations aggregation occurred, and below .5 mM salt,electrostatic repulsions become quite large and perhaps destroy the native structure. Similar transitions with salt have been observed and put into a more current context (23,24,25). Consequently, we have generally confined our scattering studies to the plateau region around 1 mM salt, but we note that our measurements at lower and higher ionic strength may suggest the onset of aggregation at about 10 mM salt and denaturation below .5 mM.…”
Section: Introductionsupporting
confidence: 68%
“…The early and important work of Zubay and Doty (22) showed that the intrinsic viscosity and light scattering do not vary in a plateau between .5 and 1.5 mM salt, but that at higher concentrations aggregation occurred, and below .5 mM salt,electrostatic repulsions become quite large and perhaps destroy the native structure. Similar transitions with salt have been observed and put into a more current context (23,24,25). Consequently, we have generally confined our scattering studies to the plateau region around 1 mM salt, but we note that our measurements at lower and higher ionic strength may suggest the onset of aggregation at about 10 mM salt and denaturation below .5 mM.…”
Section: Introductionsupporting
confidence: 68%
“…For example, LI et al (14) found out that 10 .3 to 10 -2 M NaCl had no effect on C.D. It seems to influence not only the interaction between 'rods' (most probably by competing for calcium), but also the DNA-protein association manifested by the appearance of free DNA filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Olins and coworkers45 have reported a similar unfolding transition, followed by sedimentation and diffusion constant measurements, in isolated core particles over the same range of ionic strengths reported above. 44 This transition could also be followed by changes in fluorescence of an extrinsic fluorophore attached to H3.46347 The electron-microscopic studies of Oudet and c~w o r k e r s~~,~~ suggest that these apparent unfolding transitions in solution may result in the breakdown of nucleosomes into "half-nucleosomes." Such a transition has interesting biological implications and deserves further attention.…”
Section: Introductionmentioning
confidence: 99%